Re-Making Kinship. From Community to Family: A Sephardic Experience in France - Roda, Jessica (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2016)
The Sephardic Jews living in France, who use Judeo-Spanish as their heritage language, are an assimilated diasporic group that has witnessed war, assimilation and marginalization. With the increase in genealogical research in Western Society, many Sephardim have experienced a process of revitalization of memory through kin relations with people of similar descent. This complex revitalization takes form within the structure of a community cultural centre which acts as a place for re-making kinship thanks to the emotional experience of sharing a specific musical heritage. This phenomenon forces us to examine the tension between « traditional » kinship systems — embodied in the matrilineal bloodline in the case of halakhic Jewish identity — and symbolic kinship anchored in the idea of a « chosen family », to rethink kinship as a mixture between biology and culture, as well as to reconsider current anthropological debates on religion thought beyond the strict religious practices.